Effects of tannin-geopolymer impregnation on wood: leachability, biodegradation resistance and mechanical properties - Lopez-Gomez, Yeray Manuel; Barbero-Lopez, Aitor; Suvanto, Sari; Venäläinen, Martti; Haapala, Antti (Springer Nature, 2025)
Geopolymers have elicited significant attention in the field of construction and building materials due to their enhanced durability, physical load-bearing ability and chemical resistance. This study investigates the effects of geopolymer impregnation on wood, together with commercial tannin-rich bark extract Colatan GT10, which, by itself, preserves wood against decay but leaches out once the wood is exposed to water. The efficacy of the treatments is evaluated through attenuated total reflectance Fourier transform infrared (ATR FTIR) spectroscopy, mechanical testing, decay resistance assessment (EN 113) and leachability analysis (EN 84). The results showed that the two-step tannin-geopolymer impregnation improved the durability of wood against wood decay fungi. The mechanical properties of the treated wood specimen were not different from that of the untreated controls, and the performance of the treated wood specimen was retained after the leaching test. The FTIR revealed that the absorbance of tannin at 10 and 5% treatments was reduced after leaching, indicating the leachability of tannin. The combination of tannin at 5% with subsequent geopolymer at 4% treatment yielded the best performance, showing no significant change in absorbance before and after the leaching test. Overall, this study highlights the potential of combining tannin and geopolymer impregnation treatments to enhance the performance of wood in terms of fixation, leachability and wood decay resistance. These findings contribute to the development of a durable wood material for various applications, such as outdoor construction, where resistance to decay is a critical factor.
Keywords: wood impregnation; geopolymers